2013
DOI: 10.1002/aenm.201300660
|View full text |Cite
|
Sign up to set email alerts
|

Spray Deposition of Silver Nanowire Electrodes for Semitransparent Solid‐State Dye‐Sensitized Solar Cells

Abstract: Transparent top electrodes for solid‐state dye‐sensitized solar cells (ssDSCs) allow for fabrication of mechanically stacked ssDSC tandems, partially transparent ssDSCs for building integration, and ssDSCs on metal foil substrates. A solution‐processed, highly transparent, conductive electrode based on PEDOT:PSS [poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate)] and spray‐deposited silver nanowires (Ag NWs) is developed as an effective top contact for ssDSCs. The electrode is solution‐deposited using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 50 publications
2
102
1
Order By: Relevance
“…Solutionprocessed AgNWs have recently attracted substantial attention as a transparent electrode for various organic as well as inorganic photovoltaic devices. [32][33][34][35][36][37][38] The outstanding optoelectronic properties and successful device demonstrations encourage us to further exploit the application of AgNWs as a window electrode for our tandem devices. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Solutionprocessed AgNWs have recently attracted substantial attention as a transparent electrode for various organic as well as inorganic photovoltaic devices. [32][33][34][35][36][37][38] The outstanding optoelectronic properties and successful device demonstrations encourage us to further exploit the application of AgNWs as a window electrode for our tandem devices. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3 †), probably due to the fact that the non-ohmic contact between the PC 60 BM and AgNWs is presenting an energy barrier for charge extraction. 29 Recently, we have found that ZnO nanoparticles as an electron transport layer in organic solar cells showed excellent compatibility with thermally evaporated Ag as well as with solution-processed AgNW top electrodes (Fig. S4 †).…”
mentioning
confidence: 99%
“…22,23 The use of AgNWs as bottom and/or top transparent electrodes has recently been demonstrated in polymer solar cells, dyesensitized solar cells, copper indium gallium diselenide and silicon solar cells. [22][23][24][25][26][27][28][29] However, the sensitivity to the surface that the perovskite crystals grow on and the incompatibility between the electrode and the adjacent interface layers have hindered the progress of the implementation of liquid-phase coated electrodes for perovskite solar cells. 30 In this work, through rational interface engineering in combination with judicious selection of deposition techniques, we demonstrate for the first time facile solution processing of AgNWs as top electrodes for efficient semitransparent perovskite solar cells.…”
mentioning
confidence: 99%
“…In recent years there have been a number of emerging TC materials studied in the literature ranging from metal nanowires (Au, Ag, Cu) (8)(9)(10)(11), conducting carbon allotropes (graphene, carbon nanotubes) (12)(13)(14)(15), conducting polymers (16,17), and other hybrid approaches (18). Recent attempts using metal nanotroughs by Wu et al have resulted in superior optoelectronic properties with a sheet resistance of 2 Ω/□ at 90% transmission (19).…”
mentioning
confidence: 99%